Knowledge Regarding Management of Hypertension Among Teachers at State Senior High School in Paccerakang Village - Darwis Darwis; Kartika Sari Wijayaningsih; Ratna Ratna (Poltekkes Kemenkes Palu, 2023)
The high rate of hypertension causes the high mortality rate. Hypertension can cause various complications, especially if the high incidence of hypertension is associated with a lack of knowledge about proper management of hypertension. This study aims to describe knowledge about management of hypertension. This was a quantitative descriptive study. The population in this study was all teachers at State Senior High School in Paccerakang Village who had hypertension with a total population of 50 people. 50 samples were selected using total sampling technique. Data were collected using a questionnaire and were analyzed using univariate analysis. The study findings were categorized into good, moderate and poor. The results of the study revealed that 52.5% of respondents had a poor level of knowledge regarding management of hypertension. Poor level of knowledge can be seen from the answers of respondents who stated the inappropriate management of hypertension. Based on the results of the study, it was found that more than half of respondents had a poor level of knowledge. Thus, there should be further efforts which involved coordination with the local Community Health Center to provide health education about hypertension management for State SHS Teachers in Paccerakang Village.